PENDAPATAN NASIONAL DAN PERTUMBUHAN EKONOMI SERTA DAMPAKNYA TERHADAP KETENAGAKERJAAN DAN PENGANGGURAN DI INDONESIA - Sumanti; Maryulis; Ratna Juita; Marni Nelvi; Ira Maya Sofa; Afri Rahmat (STKIP Subang, 2025)
This article examines the relationship between national income, economic growth, and labor market conditions in Indonesia. National income reflects a country’s capacity to produce goods and services, while economic growth indicates changes in production levels over time. The main focus of this study is to analyze how increases in national income and economic growth affect employment absorption and unemployment rates in Indonesia. This article employs a literature review approach by analyzing recent academic studies and official statistical data. The findings indicate that although Indonesia has maintained relatively stable economic growth, its impact on employment creation remains limited due to structural issues in the labor market, such as skill mismatch and the dominance of capital-intensive sectors. Therefore, inclusive and labor-absorbing economic growth is essential to reduce unemployment and improve overall labor market performance in Indonesia.